Phenotypic plasticity in habitat use and growth of the European eel (Anguilla anguilla) in transitional waters in the Mediterranean area - CAPOCCIONI, FABRIZIO; CICCOTTI, ELEONORA; Lin, DY; Iizuka, Y; Tzeng, WN (Ecology of Freshwater Fish, 2014)
Lagoons and estuaries are transitional waters (TW), saline in character but substantially influenced by freshwater (FW) flows and the most productive habitat after upwelling areas. The European eel, Anguilla anguilla, is a typical inhabitant of these habitats and a target of important lagoon fisheries since ancient times. Notwithstanding this, in the Mediterranean region, where the numerous coastal lagoons are the most eligible habitat for this species, eel habitat use and growth, which display a high inter-individual variability, are poorly studied. To gain knowledge about the migratory behaviour and the relative growth history of this species in TW in the Mediterranean area, the otolith Sr/Ca ratios of 56 individuals were analysed. The study sampling sites were two typical coastal lagoon environments, Caprolace lagoon and Lesina lagoon, located, respectively on the Tyrrhenian and the Adriatic coast of Italy, and the Tiber River (TR) estuary, in Central Italy. Otolith Sr/Ca profiles revealed that in all the sites, the resident contingent is substantial, while the proportion of nomad eels, or habitat inter-shifter, was different among sites. Mean annual grow rate of resident eels is higher in productive environments (TR and lagoon of Lesina), while in Caprolace lagoon, an oligotrophic lagoon, resident eels grow slower. The observed patterns of habitat use and growth seem linked to local ecological conditions: facultative movements of eels with a nomadic behaviour seem affected by food availability rather than by the salinity gradient. This consideration supports the hypothesis that the facultative catadromous migration of European eel in Mediterranean TW, and the trophic shifts that this species exhibits, depend primarily on the productivity of the environment rather than on its salinity gradient.